Efficacy of a novel formulation of L-Carnitine, creatine, and leucine on lean body mass and functional muscle strength in healthy older adults: a randomized, double-blind placebo-controlled study. Issue 1 (December 2017) - Evans, Malkanthi; Guthrie, Najla; Pezzullo, John; Sanli, Toran; Fielding, Roger; Bellamine, Aouatef
Abstract Background Progressive decline in skeletal muscle mass and function are growing concerns in an aging population. Diet and physical activity are important for muscle maintenance but these requirements are not always met. This highlights the potential for nutritional supplementation. As a primary objective, we sought to assess the effect of a novel combination of L-Carnitine, creatine and leucine on muscle mass and performance in older subjects. Method Forty-two healthy older adults aged 55–70 years were randomized to receive either a novel L-Carnitine (1500 mg), L-leucine (2000 mg), creatine (3000 mg), Vitamin D3 (10 μg) (L-Carnitine-combination) product (n  = 14), L-Carnitine (1500 mg) (n  = 14), or a placebo (n  = 14) for eight weeks. We evaluated body mass by DXA, upper and lower strength by dynamometry, and walking distance by a 6-min walk test at baseline and after eight weeks of intervention. These measures, reflecting muscle mass, functional strength and mobility have been combined to generate a primary composite score. Quality of life, blood safety markers, and muscle biopsies for protein biomarker analysis were also conducted at baseline and the end of the study. Results The primary composite outcome improved by 63.5 percentage points in the L-Carnitine-combination group vs. placebo (P  = 0.013). However, this composite score did not change significantly in the L-Carnitine group (P =  0.232), and decreased slightly in the placebo group (P =  0.534). Participants supplemented with the L-Carnitine-combination showed a 1.0 kg increase in total lean muscle mass (P  = 0.013), leg lean muscle mass (0.35 kg, P =  0.005), and a 1.0 kg increase in lower leg strength (P  = 0.029) at week 8. In addition, these increases were significant when compared to the placebo group(P =  0.034, P =  0.026, andP =  0.002, respectively). Total mTOR protein expression was increased in participants in the L-Carnitine-combination group at the end of the study compared to the baseline (P  = 0.017). This increase was also significant when compared to the placebo (P =  0.039), suggesting that the increase in muscle mass and strength was due to new protein synthesis and mTOR pathway activation. Conclusions The trial did reach its primary objective. L-Carnitine combined with creatine and L-leucine significantly improved the composite score which reflects muscle mass and strength, at the end of the study compared to placebo. The combination showed an increase in mTOR protein level, a driver for increased muscle mass which translated to an improvement in muscle strength. This new combination may provide a potential nutritional intervention to promote muscle growth and improved physical functioning in older adults.